(untitled) (Research, Society and Development, 2023)
The use of medicinal plants as an alternative or complementary treatment is very common in society, including among people living with HIV. There are studies that address clinically significant drug interactions with antiretroviral drugs, increasing the risk of negative outcomes such as toxicity or loss of virological control. So, we aim to carry out a survey on RENISUS plants that can interact with antiretrovirals used to treat HIV infection and cause harmful effects. Eighteen plant species with the potential for drug interactions with antiretroviral drugs for HIV were found. This study provides scientific evidence on possible interactions between anti-HIV drugs and medicinal plants, contributing to the expansion of collective and individual care for people with chronic diseases, such as people living with HIV/AIDS on antiretroviral therapy.